Penganiayaan Dan Perlakuan Yang Tidak Semestinya Terhadap Anak - Randi, Randi; Khusnul Hatimah, Ani; Safrina, Nabilla; Rahmansyah, Rahmansyah (DAWUH : Islamic Communication Journal, 2023)
Because of their status as relatively helpless members of the family system, children are most at risk of being subjected to the aggressive behavior of their parents or other older family members. As Tedeschi and Felson (1994, p. 287) have noted, "those who very rarely use force against others consider their children to be a delightful business." In this section we will examine the prevalence and consequences of four main forms of child abuse, namely physical abuse, sexual violence, and inappropriate verbal and mental psychological abuse.